Isolation and characterization of Saccharomyces cerevisiae mutants with a different degree of resistance to killer toxins K1 and K2 - Flegelová, Hana; Novotná, Drahomíra; Vojtísková, Katerina; Janderová, Blanka (FEMS yeast research, 2002)
Killer toxin K1 of Saccharomyces cerevisiae kills sensitive cells of the same species by disturbing the ion gradient across the plasma membrane after binding to the receptor at cell wall beta-1,6-glucan. Killer protein K2 is assumed to act by a similar mechanism. To identify the putative plasma membrane receptors for both toxins we mutagenized three sensitive S. cerevisiae strains and searched for clones with killer-resistant spheroplasts. The well diffusion assay identified three phenotypically different groups of clones: clones resistant simultaneously to both toxins, clones with lowered sensitivity to only K1 toxin and those with strongly lowered sensitivity to K2 and partially lowered sensitivity to K1 toxin. These phenotypes are controlled by recessive mutations that belong to at least four different complementation groups. This indicates certain differences at the level of interaction of K1 and K2 toxin with sensitive cells.
Keywords: Microbial Sensitivity Tests; Membrane Proteins; Genetic Complementation Test; antibiotická rezistence; Killer Factors, Yeast; mutace; mykotoxiny; mikrobiální testy citlivosti; Mycotoxins; Spheroplasts; receptory buněčného povrchu; sféroplasty; Receptors, Cell Surface; killer faktory kvasinek; Saccharomyces cerevisiae; membránové proteiny; Drug Resistance, Microbial; Mutation; testy genetické komplementace